Cytomegalovirus impact on elderlies’ vaccination response - Abdull Jalil, Mohd Asyraf; Mohd Yusof, Nazri (IIUM Press, International Islamic University Malaysia, 2017)
Disease burden from the Malaysian elderly population is increasing as demographics shifts towards longer life expectancy. It is increasingly evident that immunosenescence is the central process in many age-related illnesses. Latent human cytomegalovirus (HCMV) infection had been shown to change the immune system in similar ways to aging, by causing chronic antigenic stress. However, direct evidence on the impact of such changes on health remains contentious due to limited data, variable population backgrounds and individual responses to HCMV. In this study among 59 elderly people in Kuantan, the impact of host HCMV control (measured using HCMV IgG level) on immunosenescence was assessed using Influenza vaccination response via haemagglutination inhibition (HI) assay. A criterion of ≥ fourfold rise in titre and a titre of ≥ 40 was used as an indicator for good response. Effect of chronic co-morbidities and history of significant infection was also studied as contributing factors. It was found that high HCMV IgG levels (> 90 RU/ml) was significantly associated with lower response rate to three vaccine strains (χ2(1) = 6.720, p = 0.010).